ENDOCARDITIS (Neo Scientific Peer Reviewed Journal, 2026)
Endocarditis is an infection of the inner lining of the heart, often involving heart valves. This article explores its pathophysiology, risk factors, clinical manifestations, diagnostic methods, treatment options, and prevention strategies, providing a comprehensive overview of this serious condition.